2015
DOI: 10.1039/c5ra12691f
|View full text |Cite
|
Sign up to set email alerts
|

nBu4NI-catalyzed intermolecular C–O cross-coupling reactions: synthesis of alkyloxyamines

Abstract: nBu4NI-catalyzed cross-coupling of benzyl and allylic compounds with N-hydroxyphthalimide for the synthesis of alkyloxyamines were realized for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“… , A disadvantage of this method is that the arene or alkene substrate needs to be added in a large excess (10 equiv). The same transformation was also realized using cerium­(IV) ammonium nitrate (CAN) or tert -butylhydroperoxide (TBHP) and tetrabutylammonium iodide (TBAI) or other (transition) metals as co-oxidants. Of note, with TBHP/TBAI, tert -butoxyl radicals are generated, which can also engage in benzylic C–H abstraction .…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“… , A disadvantage of this method is that the arene or alkene substrate needs to be added in a large excess (10 equiv). The same transformation was also realized using cerium­(IV) ammonium nitrate (CAN) or tert -butylhydroperoxide (TBHP) and tetrabutylammonium iodide (TBAI) or other (transition) metals as co-oxidants. Of note, with TBHP/TBAI, tert -butoxyl radicals are generated, which can also engage in benzylic C–H abstraction .…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…The reaction of ethyl acetoacetate 43 with benzylamine 44 in the presence of n-Bu4NI catalyst (20 mol%), and an oxidant (4.0 equiv.) to have the product 45 with good yield as explained in table 4 The mechanism of the cascade reaction [120] was explained by Ishihara and co-workers, [121] suggested that the active iodine species ammonium hypoiodite ( The aerobic C-H oxidation of C(sp3)-H activation by organocatalytic (metal free) recyclable catalyst TEMPO. TEMPO one of the most choice in industry [122] and has been widely used for the oxidation of alcohols to carbonyls, [123,124], and it use in the oxidative functionalization of other functionalities represents an important challenge and the examples are very limited [125][126][127][128][129][130][131].…”
Section: C-h Bond Oxidationmentioning
confidence: 99%
“…Precursor 2 and R 1 ONH 2 were synthesized as literature report. [18][19][20] All of the yields were not optimized.…”
Section: Instruments and Materialsmentioning
confidence: 99%